Preliminary strontium isotope (87Sr/86Sr) baselines for the Bjäre Peninsula and Halland in southern Sweden - Macheridis, Stella; Sandstrom, Michael; Svensson, Andreas; Wilhelmson, Helene; Berggren, Åsa; Wranning, Per (Frontiers in Environmental Archaeology, 2024)
During the last decade, the application of strontium isotope analysis ( 87 Sr/ 86 Sr) has increased rapidly. The understanding of the strontium isoscape and the construction of a strontium isotope baseline in southern Scandinavia is biased towards Denmark and southwestern to eastern Scania. We report the results of new baseline samples in Halland and Bjäre peninsula, adding to the rich strontium isotope library that exists for southern Scandinavia. We nuance the previous divisions of Scania, in which the Bjäre peninsula is not well represented. The results show that Bjäre peninsula is characterized by relatively low 87 Sr/ 86 Sr values gathered in the preliminary baseline 0.7100 ± 0.0024 (2σ, n=8), similar to that of southwest Scania and to Zealand in Denmark. There is a greater variation, and higher values, among the Halland samples. Together with previously published faunal samples, a preliminary 87 Sr/ 86 Sr baseline for Halland is 0.7122 ± 0.0058 0055 (2σ, n=1524). We apply these baseline results on archaeological cases, both human and animal, from recent excavations in the Bjäre peninsula. The results imply that there was a certain degree of mobility and interaction across the landscape in this region of southern Scandinavia in prehistory.